Improved Accessibility for People With Disabilities at the Sheikh Zayed Grand Mosque Using a Universal Design Approach - Bambang Suhardi; Muhammad Fawaid Nurazizi; Irwan Iftadi (Journal of Islamic Architecture, 2024)
People with disabilities must be considered as one of the Sheikh Zayed Grand Mosque user groups. This happens because of the lack of accessible facilities and it is not in accordance with the standards set by the government. Therefore, it is necessary to conduct a research to determine whether the Sheikh Zayed Grand Mosque has met the accessibility criteria. The research aims to determine the accessibility of the Sheikh Zayed grand mosque. The results of the assessment are used as a basis for making improvements in the mosque accessibility. The method used is filling out an accessibility check sheet. The checklists are developed from the regulation of the Minister of Public Works and Housing of the Republic of Indonesia number 14/PRT/M/2017 and universal design. The level of accessibility is also determined based on the same regulation and universal design. The areas studied include: circulation/corridor, entrance/exit, ramp, stair/lift, handrail, wudu area, toilet, prayer room, parking area, as well as signs and information. The results of the accessibility index assessment showed that six areas of the mosque were categorized as accessible, two areas of the mosque were categorized as less accessible, and two areas of the mosque were categorized as inaccessible. Proposed improvements were made to the circulation area, ramps, stairs/elevators, handrails, wudhu areas, toilets, prayer rooms, parking areas, as well as signs and information.